Coping strategies to prevent or reduce stress and burnout among oncology physicians: a systematic review - Anne Calbusch Schmitz; Camila da Rosa Witeck; Julia Meller Dias de Oliveira; Mark Clemons; Carlos Eduardo Paiva; Andre Luís Porporatti; Graziela de Luca Canto; Suely Grosseman (Brazilian Journal of Oncology)
The purpose of this systematic review (SR) was to identify interventions that are effective to prevent or reduce stress and burnout among oncologists. Search was conducted in eight electronic databases and grey literature databases, with no language or time restrictions. Included studies involved medical oncologists and contained interventions to prevent or deal with stress or burnout with outcomes assessment. In two selection phases process, 19 out of 3,020 studies were included. Risk of bias was low for nine studies, moderate for six studies and high for four ones. Certainty of evidence was considered low and very low for the analyzed outcomes. Interventions varied a lot and those which had a significant effect in stress and burnout reduction among oncologists were experience sharing between female doctors in virtual groups, integrative meetings outside the work environment, and team sessions supervised by counselors. Although interventions had variable effects on reducing or preventing burnout and stress, mores studies are needed due to outcomes low evidence.